TANGGAPAN PERTUMBUHAN TEBU MUDA (Saccharum officinarum L.) TERHADAP SERANGAN LARVA Lepidiota stigma Fabricius - , FAJAR ARIF EKO WIBOWO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of the obstacle to get high production of sugarcane is white grub attack (Lepidiota stigma Fabricius). The aims of this research are to find the sugarcane growth that attacked by white grub and comparing the attack of white grub in between young and the older plant. This research was conducted in green house used completely randomized design. This research used second phase larva of white grub and it was applied in three kinds of sugarcane plant ages (9, 11, and 13 lifespan weeks) and the checked treatment (without white grub application). This research test conducted by releasing one white grub in every single pot that has been planted a young sugarcane plant before. The plant was observed from t=0 (before application) until 5 weeks after application. The results showed that sugarcane shoot still can growth well but dry root mass decreased and increased in the end of observation week. Sugarcane shoot still can growth well because of white grub attack did not influence a lot in sugarcane growth and dry root mass increased in the end of observation week because the white grub in change phase to be third phase so it did not need eat too much. White grub ate amount 5.75 g of dry mass root in 5 weeks. The conclusions are white grub did not influence a lot in sugarcane shoot growth and planting sugarcane early can minimize of sugarcane damage.